The mediating role of organizational culture in the relationship between total quality management and organizational performance in the UAE - Al Hamd, Abdulla Esam (2023)
Total quality management (TQM) is important for the improvement of performance and organizational culture. However, prior literature showed that there are mixed results on the effect of TQM on organizational culture and performance. In addition, most of prior literature focused on the developed nations. The purpose of this study is to examine the effect of TQM on organizational culture and organizational performance. In addition, the study examines the mediating role of organizational culture between TQM and the organizational performance of Abu Dhabi Agriculture and Food Safety Authority (ADAFSA) divided into three branches (Abu Dhabi, Alain, Al Dhafra). Building on the TQM models and the contingency theory, the study proposed that TQM has a positive effect on organizational culture and organizational performance. Organizational culture is expected to affect positively the organizational performance and mediate the effect of TQM on organizational performance. In this quantitative research work, a structured questionnaire was used as the instrument for data collection with a sample of 54 branches represented by senior employees and managers from ADAFSA. The validity and reliability of the measurement and structural models were established; PLS-SEM was used to test the hypotheses of the study. The results showed that there was a significant and positive effect of TQM on organizational culture and organizational performance. In addition, the results revealed that organizational culture affected positively organizational performance and mediated the effect of TQM on organizational performance. Decision makers are recommended to improve the implementation of TQM and to establish a culture based on a fair process of promotion, cooperation, and respect. Future work can extend the findings of this study by examining the TQM in the context of other organizations and other countries